Improvement of Pedagogical Skills of Physical Education Teachers in the Process of Training and Re-Training - Musajanovich, Mirzakulov Isajan; Dilshotovich, Akhmetov Rustam; Khamidulloevich, Rakhmatov Jasur (European Journal of Life Safety and Stability (2660-9630), 2023)
This article presents several ideas on the development of the system of training and retraining of teachers and trainers today. Also, the relevance of several decisions and decrees related to the process in our Republic is given, through these legal documents, it is necessary to educate teachers and trainers of the field as personnel suitable for the needs of the times.